(untitled) (Journal of Philosophy Culture and Political Science, 2019)
This article discusses the main issues of civic identity and place in the formation of a stable state. The author argues that the civic identity is the basis for the formation and development of civil society as a guarantee of democracy. Highly developed and independent civil society is a good and necessary to the core of the system of public institutions and effective market economy. For the emergence of civil society must have the rights of individuals. This implies that the source of civil society is man himself. Personality of the opportunity to realize their interests. This in turn is a key indicator of civil society. In such a society a person lives, not for the state, a state exists for the sake of the citizen.